2011
DOI: 10.1038/tp.2011.59
|View full text |Cite
|
Sign up to set email alerts
|

A common and functional mineralocorticoid receptor haplotype enhances optimism and protects against depression in females

Abstract: Mineralocorticoid (MR) and glucocorticoid receptors (GR) are abundantly expressed in the limbic brain and mediate cortisol effects on the stress-response and behavioral adaptation. Dysregulation of the stress response impairs adaptation and is a risk factor for depression, which is twice as abundant in women than in men. Because of the importance of MR for appraisal processes underlying the initial phase of the stress response we investigated whether specific MR haplotypes were associated with personality trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
80
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(87 citation statements)
references
References 55 publications
5
80
1
1
Order By: Relevance
“…However, if our findings hold in patient samples, we suggest that the shift is dependent on MR-activation and might be prevented by short-term administration of MR antagonists. Related to this suggestion, more recent studies associated genetic variants in the gene encoding the MR with interindividual differences in risk for psychopathology (69)(70)(71)(72). Our findings could have mechanistic implications for understanding of the impact of stress on daily life and mental wellbeing, which might be particularly prominent in individuals with high MR sensitivity.…”
Section: Discussionmentioning
confidence: 53%
“…However, if our findings hold in patient samples, we suggest that the shift is dependent on MR-activation and might be prevented by short-term administration of MR antagonists. Related to this suggestion, more recent studies associated genetic variants in the gene encoding the MR with interindividual differences in risk for psychopathology (69)(70)(71)(72). Our findings could have mechanistic implications for understanding of the impact of stress on daily life and mental wellbeing, which might be particularly prominent in individuals with high MR sensitivity.…”
Section: Discussionmentioning
confidence: 53%
“…Indeed, it has been repeatedly shown that depressed patients exhibit decreased MR expression in hippocampus and prefrontal cortex in post-mortem studies (Klok et al, 2011a;Medina et al, 2013;Qi et al, 2013). Furthermore, polymorphisms and haplotypes of the MR gene have been shown to be associated with depression (Klok et al, 2011b) and to moderate the association between childhood neglect and amygdala reactivity (Bogdan et al, 2012). Also, there was an attenuated cortisol inhibition in psychotic major depression after fludrocortisone also consistent with impaired MR function in these patients (Juruena et al, 2013;Lembke et al, 2013).…”
Section: Discussionmentioning
confidence: 75%
“…Four NR3C1 gene SNP (ER22/23EK, N363S, BclI C/G, and A3669G) and 2 NR3C2 gene SNP (À2 G/C and MR I180V) have been described to influence the transactivation ability of their receptors, resulting in changes in sensitivity to glucocorticoids, including cortisol [18,19]. Importantly, the same genetic variants in the NR3C1 gene were associated with bone mineral density, body mass index, abdominal obesity, and total cholesterol under nonstress conditions [16].…”
Section: Introductionmentioning
confidence: 87%